Фінансові важелі реалізації принципу соціальної відповідальності бізнесу в гірничо-металургійній промисловості - Галушко, О.С. (Економіка промисловості, 2013)
Розглянуто сучасний стан та особливості соціальної відповідальності бізнесу в гірничо-металургійному комплексі України. Обґрунтовано визначення рівня соціальної відповідальності по мінімальному значенню локальних показників. На основі аналізу рівня соціальної відповідальності та авторського методичного підходу до його оцінки, обґрунтовано, що соціальна відповідальність має свій вияв тільки у разі впливу соціально спрямованих дій бізнесу на фінансові результати роботи підприємства. Запропоновано фінансові важелі подальшого розвитку соціальної відповідальності бізнесу в гірничо-металургійному комплексі України.
Ключові слова: соціальна відповідальність, бізнес, підприємства гірничо-металургійного комплексу, оцінка рівня соціальної відповідальності бізнесу, фінансові важелі. Рассмотрено современное состояние и особенности социальной ответственности бизнеса в горно-металлургическом комплексе Украины. Обоснованы методические подходы к определению уровня социальной ответственности по минимальному значению локальных показателей. На основе анализа уровня социальной ответственности и авторского методического подхода к его оценке обосновано, что социальная ответственность имеет место только в случае положительного влияния социально направленных действий бизнеса на финансовые результаты работы предприятия. Предложены финансовые рычаги дальнейшего развития социальной ответственности бизнеса в горно - металлургическом комплексе Украины.
Ключевые слова: социальная ответственность, бизнес, предприятия горно-металлургического комплекса, оценка уровня социальной ответственности бизнеса, финансовые рычаги. The role of mining and metallurgical complex in providing the level of socio-economic development of regions and Ukraine is considered. The current status and characteristics of social responsibility in the mining and metallurgical complex of Ukraine are analyzed.
On the basis of the analysis of official statistics the low level of corporate social responsibility in the mining and metallurgical complex of Ukraine was defined. It is reflected in directing over 80 percent of steel production on export, and as a consequence, in disregarding the national interest in creation and upgrading the capacity of domestic economy. As a result of these actions increase in import in almost all sectors of the economy of Ukraine and increase in the trade deficit affect the number of jobs, unemployment rate, public debt and exchange rate.
On the basis of the analysis of current state of the problem of social responsibility in the world it is found out that theoretical studies have been practically reflected in international regulations such as the UN Global Compact principles and standards of ISO. However, the recommendation of these documents does not intensify social responsibility of business. The author follows the concept that business can take socially oriented decision only in the case of creation of such state legislation that would allow businesses to obtain economic benefits from the adoption and implementation of socially-oriented solutions.
The author has substantiated that determination of the level of social responsibility should be conducted by the minimum value of local indicators because low levels of any of them show contempt for human rights.
In the conclusion basing on the impact of changes in the legislation of Ukraine (including the tax legislation) on the adoption of socially-oriented business solutions, as well as on the author’s methodological approach to evaluation of the level of social responsibility it is underlined that the leverages for enhancing social responsibility should affect the financial performance of mining and metallurgical complex of Ukraine.
It is defined that further researches in the field of determining the ways for improvement of corporate social responsibility in the mining and metallurgical complex of Ukraine should be performed in a scientific substantiation of harmonization of legislation in terms of creation of incentives and sanctions that will allow Ukraine to develop as a welfare state.
Keywords: social responsibility, business, enterprisesof mining and metallurgical complex, determination of level of business social responsibility, financial leverages.